Development and content validation of the Safe Surgery Organizational Readiness Tool: A quality improvement study. (May 2021) - Hayirli, Tuna C.; Meara, John G.; Barash, David; Chirangi, Bwire; Hellar, Augustino; Kenemo, Benard; Kissima, Innocent; Maongezi, Sarah; Reynolds, Cheri; Samky, Hendry; Ulisubisya, Mpoki; Varallo, John E.; et al.
Abstract: Background: Recent efforts to increase access to safe and high-quality surgical care in low- and middle-income countries have proven successful. However, multiple facilities implementing the same safety and quality improvement interventions may not all achieve successful outcomes. This heterogeneity could be explained, in part, by pre-intervention organizational characteristics and lack of readiness of surgical facilities. In this study, we describe the process of developing and content validating the Safe Surgery Organizational Readiness Tool. Materials and methods: The new tool was developed in two stages. First, qualitative results from a Safe Surgery 2020 intervention were combined with findings from a literature review of organizational readiness and change. Second, through iterative discussions and expert review, the Safe Surgery Organizational Readiness Tool was content validated. Results: The Safe Surgery Organizational Readiness Tool includes 14 domains and 56 items measuring the readiness of surgical facilities in low- and middle-income countries to implement surgical safety and quality improvement interventions. This multi-dimensional and multi-level tool offers insights into facility members' beliefs and attitudes at the individual, team, and facility levels. A panel review affirmed the content validity of the Safe Surgery Organizational Readiness Tool. Conclusion: The Safe Surgery Organizational Readiness Tool is a theory- and evidence-based tool that can be used by change agents and facility leaders in low- and middle-income countries to assess the baseline readiness of surgical facilities to implement surgical safety and quality improvement interventions. Next steps include assessing the reliability and validity of the Safe Surgery Organizational Readiness Tool, likely resulting in refinements. Highlights: Variety of organizational readiness tools exist, but none that are designed for surgery in low- and middle-income countries. Literature review, qualitative findings, and expert feedback were combined to identify essential domains and survey items. Domains and item content validity were assessed through panel review. A theory- and evidence-based organizational readiness assessment tool was created.